Inovasi Investasi Keuangan Haji Pada Sektor UMKM Sebagai Strategi Peningkatan Kemudahan Berusaha dan Daya Saing Ekonomi Indonesia pada Masa Pandemi Covid-19 - Purwanto Putra (Administratio, 2021)
This research analyzes the possibility of hajj fund investment innovation in the field of superior product-based increasing ease of doing business (Ease of Doing Business) and competitiveness of the Indonesian economy. At the same time, we will try to examine the potential benefits of the UMKM hajj fund investment for the community and economic recovery after Covid-19. This research was conducted using a qualitative approach with descriptive methods. Descriptive method is used to provide a detailed description or explanation of a problem. Collecting data in this study using the information literacy method, the information literacy model used is The Seven Pillars of Information Literacy. The results show that investing in the MSME sector has several advantages that can be optimized with the availability of supporting regulations and the choice of products and strategies for implementing MSMEs that are potential to be developed. The MSME sector has potential benefits with shared risks, such as the parable, "don't put eggs in one basket". So it can be said to be an innovation when the risk of investing in Hajj funds can be minimized with a deployment strategy. Another result of hajj financial investment in the MSME sector is also very compatible to be implemented with kafah (comprehensive) sharia.